Communication barriers in the workplace: A study in educational institutions - Nonche, Rudiansah; Abd Malek, Marwa (Jurnal Penyelidikan Sains Sosial, 2026)
Effective communication is a key for organisational success, yet many barriers can limit it, leading to poor employee performance. Therefore, this study was conducted to identify the main barriers to effective communication among colleagues. This study used quantitative approach through an online questionnaire. Respondents were all staff members of Kolej Komuniti Sandakan. Findings showed an interesting insight, where physical and environmental barriers caused the most impact to poor communication. There were issues related to digital communication tools they are using, poor internet connectivity, improper workspace layout, noise distractions, and physical distance between units. Furthermore, psychological and emotional barriers also lead to communication barriers. It is largely due to work stress, negative attitudes among colleagues, and personal conflicts. Cultural and perceptual barriers also affect communication, where individuals understand messages in different ways, messages are interpreted based on personal perceptions, staff avoid expressing disagreement, and cultural norms of not to speak out. In addition, organisational and hierarchical barriers was also found to give effect to poor communication. It is due to message changes when passed through multiple people and too many hierarchy layers slow down communication. Language and semantic barriers were the least problematic, though some messages were unclear due to inappropriate word choice. This study recommends top management to upgrade and standardise digital communication tools to ensure reliability and ease of use, as well as improving internet infrastructure. Workspace layouts should be reviewed, and regular online meetings should be scheduled to maintain consistent communication. Stress management programme and team building are crucial to help improve relationships, reduce negative attitudes, and resolve personal conflicts among colleagues. Cultural awareness training can help staff understand different communication styles and perspectives. Important information should be communicated directly through official platforms or written documentation to ensure consistency and reduce distortion, hence promoting a good communication practice.